2020
DOI: 10.1167/tvst.9.5.16
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Comparison of Algorithms for Detection of Primary Angle Closure Suspect Based on Static and Dynamic Anterior Segment Parameters

Abstract: Establishment and comparison of algorithms for detection of primary angle closure suspect based on static and dynamic anterior segment parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…In our previous studies, we reported an AUC of 0.844 with inclusion of angle recess area at 750 lm, anterior chamber volume, lens vault and iris cross-sectional area change / pupil diameter change after physiologic mydriasis in the prediction model for detection of PACS (Zhang et al 2020).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our previous studies, we reported an AUC of 0.844 with inclusion of angle recess area at 750 lm, anterior chamber volume, lens vault and iris cross-sectional area change / pupil diameter change after physiologic mydriasis in the prediction model for detection of PACS (Zhang et al 2020).…”
Section: Discussionmentioning
confidence: 95%
“…In our previous studies, we reported an AUC of 0.844 with inclusion of angle recess area at 750 μm, anterior chamber volume, lens vault and iris cross‐sectional area change / pupil diameter change after physiologic mydriasis in the prediction model for detection of PACS (Zhang et al. 2020 ). In the future study, we tend to investigate the demographic, ocular anatomical and dynamic risk factors associated with the development of angle closure.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 26 , 27 have developed several algorithms for detecting PAC using AS-OCT by mechanisms of angle closure: pupillary block, plateau iris configuration, thick peripheral iris roll, and all three mechanisms. The authors measured 12 anterior segment parameters twice under different lighting conditions.…”
Section: Discussionmentioning
confidence: 99%
“… Lens vault seems to increase with a larger pupil, which also seems to happen in the real eye but with a lesser magnitude. 24 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we had investigated algorithms for detection of PACS by combining static and dynamic ASOCT parameters and found that the three algorithms including BLR, NBC and NN failed to meet the requirements for population‐based screening of PACS; NN had the largest AUC of 0.844 (Zhang et al 2020 ). The current investigation shows potential for the development of an image‐based non‐contact method to screen for PACS, which is the ASOCT examinations under both light and dark conditions.…”
Section: Discussionmentioning
confidence: 99%